Efeito da terapia fotodinâmica no tratamento da halitose em adolescentes – ensaio clínico e microbiológico - Ciarcia, Ana Carolina Costa da Mota (2015)
Halitosis is the term used to describe an unpleasant odor that emanates from the oral cavity or breath. It main cause is in the oral cavity, being 51% of cases related to the presence of tongue coating, resulting from the degradation of organic substrates for anaerobic bacteria and the production of volatile sulfur compounds (VSC). It is believed that the primary source of exhalation of these compounds is in the back of the tongue. The conventional treatment of halitosis is the chemical and mechanical removal of microorganisms with rinses and scrapers, but there is much disagreement in studies on the effectiveness of these methods. Photodynamic therapy involves the use of a dye and a light source of a specific wavelength which has an antimicrobial action. The objective of this study was to evaluate the clinical and microbiological effect of photodynamic therapy for the treatment of halitosis in adolescents between 12 and 19 years. 46 adolescents were randomly divided into three groups: Group 1 treatment with photodynamic therapy, group 2 with tongue scraper and group 3 associations of treatments. Clinical evaluation of halitosis were made by means of gas chromatography and microbiological testing by counting colony forming units per ml (CFU / ml). It was used the Kruskal-Wallis tests for comparison followed by the Student-Newman-Keuls test. To check colony forming units per ml (CFU / ml) before and after treatment the ANOVA test were used. For all analyzes were considered a level significance of α = 0.05. After treatment there was a statistically significant decrease in all groups (p <0.001), but the combination of photodynamic therapy to the tongue scraper proved more effective at all hydrates of sulfur reduction (median = 0). Microbiologically it was observed a statistically significant difference before the treatment for the groups 1 and 2 (p<0,001). This study provides a new treatment option for halitosis in adolescents with immediate effect without mechanical aggression common in lingual papillae when the conventional treatment is used.